Internal Control System of On-Street Parking Retribution Based on the COSO Framework: A Case Study of the Parking Management Unit (UPT Parkir) of the Padang City Transportation Departement - Putri Alia Sakina; Agus Suryono; I Gede Eko Putra Sri Sentanu (Department of Public Administration, 2026)
On-street parking retribution is a strategic component of local own-source revenue (PAD); however, its management in Padang City continues to face potential revenue loss, as revenue realization has consistently fallen short of targets and discrepancies exist between actual field collections and officially reported remittances. This study analyzes the internal control system governing on-street parking retribution management using the COSO Framework to identify systemic weaknesses that allow potential revenue loss to persist. Employing a qualitative approach with a single-case study design at the Parking Management Unit (UPT), data were collected through semi-structured interviews, non-participant observation, and document analysis, and were analyzed using the Miles and Huberman interactive model. The findings reveal that all five COSO components have not functioned effectively: the control environment is weak, risk assessment is not conducted systematically, control activities remain largely manual, information flows are incomplete, and monitoring activities are inconsistent. These weaknesses are further exacerbated by a multi-layered collection structure involving parking attendants, parking contractors, and the Parking Management Unit (UPT). The study recommends institutional reform, digitalization of parking retribution collection, standardization of procedures, and more consistent oversight. This research contributes to the literature by demonstrating how a multi-layered collection structure and the dominance of informal relationships undermine the effectiveness of all COSO components, thereby creating systemic vulnerabilities to potential revenue loss.